Big-5 Personality Traits as Predictors of Allostatic Load in Latino Americans: A Longitudinal Study - Sevi, Baris; Supiyev, Adil; Gutierrez, Angela; Graham, Eileen K.; Mroczek, Daniel K.; Muniz-Terrera, Graciela (Oxford Univ Press Inc, 2025)
Objectives Allostatic load (AL) refers to the measure of cumulative wear and tear resulting from chronic stress and life events. AL presents adverse consequences for a diverse range of health conditions, and Latino populations show a high risk for elevated AL. This study aimed to test the Big-5 personality traits as possible predictors of AL in Latinos.Methods Using data from the Health and Retirement Study, we examined the Big-5 and AL connection through three time points in 8 years (Time 1 = 2006/2008; Time 2 = 2010/2012; Time 3 = 2014/2016). Only self-identified Latinos were included in the analysis sample (N = 319). Big-5 and demographics were obtained at baseline, and AL scores were computed for each time point.Results First, separate longitudinal linear mixed-effect models examined the effects of each Big-5 personality trait on AL change over time, then a fully adjusted longitudinal linear mixed-effect model was tested entering the Big-5 personality traits simultaneously. All models controlled for sociodemographic factors. Conscientiousness emerged as the only consistent significant predictor, for the separate and the simultaneous models. In baseline associations, higher conscientiousness was associated with lower AL. For predicting change in AL over time, none of the personality traits had significant associations in any of the models.Discussion The findings bolster prior evidence that conscientious can be a protective factor against elevated AL. Conscientiousness is a possible protective factor and improving related traits can be a path to achieve better health in Latino Americans.
Keywords: Latino/Hispanic Older Adults; Personality; Health; Longitudinal Design/Data Analysis